Aktivitas Antibakteri Ekstrak Akar Ceplukan (Physalis angulata L.) Terhadap Staphylococcus epidermidis dan Pseudomonas aeruginosa - Pratika Viogenta; Lilik Koernia Wahidah; Ika Harum Saputri (Fakultas MIPA Universitas Tulang Bawang Lampung, 2017)
Root ceplukan (Physalis angulata L.) is one of the medicinal plants that contain several active compounds that are antibacterial. This study aims to prove the antibacterial activity of root ceplukan extract againsts Staphylococcus epidermidis bacteria and Pseudomonas aeruginosa bacteria. Root ceplukan was extracted by maceration with ethanol 70%. Root root extracts of phytochemical screening include flavonoids, alkaloids and saponins. The ceplukan root extract was then tested against S. epidermidis and P. aeruginosa bacteria using wells method with concentrations of 20%, 40%, 60%, 80%, 100%, aquades as a negative control and amikacin as a positive control. Inhibitory zone diameter with each concentration for P. aeruginosa bacteria, among others, negative control = 0 mm, positive control = 21,623 mm, 100% = 16.9 mm, 80% = 15.05 mm, 60% = 13.703 mm, 40% = 12.02 mm, 20% = 12.02 mm and S. epidermidis bacteria have inhibitory zone at positive control of 21,623 mm. The results of this study showed that root extract ceplukan proved to have inhibition zone against bacteria P. aeruginosa at all concentrations but has no inhibition zone against S. epidermidis bacteria. Root ceplukan extract has a minimum inhibitory concentration of 14% and a minimum bacterisid concentration of 20%, against P. aeruginosa bacteria. The results of phytochemical analysis showed that root ceplukan positively contain flavonoids, alkaloids and saponins are suspected as antibacterial compounds. Keywords : Antibacterial, Staphylococcus epidermidis, Pseudomonas aeruginosa, Ceplukan root extract